2005
DOI: 10.1017/s1431927605050865
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Caprolactone Nanocapsules Morphological Features by Atomic Force Microscopy

Abstract: Polymeric nanoparticles containing an oily core, named nanocapsules (NCs), have been widely studied in the life sciences field due to their therapeutic potentialities of drug targeting in the body accompanied also by its larger stability in the biological fluids compared to other colloidal carriers. Many studies have shown different applications of nanocapsules for therapeutic use concerning their properties [1] of loading poorly water-soluble drugs, protection drugs from inactivation in the gastro-intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
10
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
8
10
0
2
Order By: Relevance
“…This observation can be explained by a possible NC flattening and aggregation process that takes place after drying on a glass surface. In fact, the flattening phenomenon was probably related to variations in polymeric wall thickness and in its homogeneity, and it is in accordance with previous works [6,22,26]. The diameter/height ratios were calculated from the topographical profile of AFM.…”
Section: Nanocapsules Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation can be explained by a possible NC flattening and aggregation process that takes place after drying on a glass surface. In fact, the flattening phenomenon was probably related to variations in polymeric wall thickness and in its homogeneity, and it is in accordance with previous works [6,22,26]. The diameter/height ratios were calculated from the topographical profile of AFM.…”
Section: Nanocapsules Characterizationsupporting
confidence: 88%
“…Values obtained in this study showed a diameter/height ratio of 12 ± 2 and 8 ± 1 for unloaded PCL NC and CS-PCL NC, indicating that the presence of CS increased the hardness of the polymeric wall, as its value is lower. Similarly to this work, Leite et al [26] and de Assis et al [6] observed a ratio of approximately 10 for PCL NC and PLA NC, respectively. When 99m Tc-MIBI was associated with the NC, the diameter/height ratios decreased to values of 4 ± 0.1 and 7 ± 1, for 99m Tc-MIBI-PCL NC and 99m Tc-MIBI-CS PCL NC, respectively.…”
Section: Nanocapsules Characterizationsupporting
confidence: 85%
“…AFM analysis in tapping mode requires only mild experimental conditions suitable for probing soft samples. Vesicular polymeric nanostructures containing an oily core have already been successfully analysed and their vesicular structure was confirmed by this method (de Assis et al, 2008;Garcia et al, 2015;Leite et al, 2005;Mosqueira et al, 2005;Pereira et al, 2008). Phase images of our NC (Figure 3) revealed differences in stiffness of the NC core (dark regions) surrounded by a shell (lighter layer).…”
Section: Morphological Characterisation Of the Nanoparticlesmentioning
confidence: 57%
“…4) (SCHAFFAZIK et al, 2003;SOUTO et al, 2012). (BENDER et al,2012;KHAYATA, et al, 2012;LEITE et al, 2005;MÜLLER et al, 2001;NECKEL & LEMOS-SENNA, 2005;SOUTO et al, 2012).…”
Section: Nanopartículas Poliméricasunclassified
“…(Adaptado de SCHAFFAZICK, et al, 2003) Nanocápsulas apresentam vantagens por terem propriedades mais flexíveis que outras nanopartículas poliméricas, transpondo espaços entre células como o endotélio vascular, além da alta estabilidade em fluídos biológicos comparadas a outros carreadores coloidais. Nanocápsulas (NCs) também têm vantagens sobre os demais sistemas no emprego em substâncias sensíveis a temperaturas acima de 40 °C e a fotodegradação(LEITE et al, 2005; MULLER et al, 2004).Em um estudo de fotoestabilidade da tretinoína, Ourique et al(2008) verificaram que suspensões de NCs contendo tretinoína apresentaram meia-vida superior a solução metanólica do fármaco e que a tretinoína contida nas NCs apresentaram menor fotodegradação. Contri et al(2011) relatam em um estudo de controle de liberação de capsaicinóides contidos em NCs, um aumento no efeito analgésico dos capsaicinóides e uma diminuição na sensação de queimação na pele.…”
unclassified